THE EFFECT OF INSTITUTIONAL OWNERSHIP AND MANAGERIAL OWNERSHIP ON CORPORATE SOCIAL RESPONSIBILITY WITH FINANCIAL PERFORMANCE AS A MODERATING VARIABLE - Immanuel, Vanecia Eveline; Imelda, Elsa (Graduate Program of Universitas Tarumanagara, 2024)
This study aims to investigate the effect of institutional ownership and managerial ownership on corporate social responsibility. The study also examines the effect of financial performance on the relationship between institutional ownership and managerial ownership on corporate social responsibility. The data used in this study is secondary data sourced from the annual reports and sustainability reports of energy, basic materials, and industrial sector listed on Indonesia Stock Exchange (IDX) during the 2020-2022. The research sample was selected using purposive sampling method in order to obtain 40 companies as samples. The data analysis used to test the hypothesis is multiple linear regression and moderated regression analysis methods using the EViews 10 software. The results show that managerial ownership has a negative and significant effect on corporate social responsibility, but the institutional ownership has no effect on corporate social responsibility. This study also indicate that financial performance cannot strengthen the relationship between managerial ownership and corporate social responsibility. Similarly, the relationship between institutional ownership and CSR fails to be strengthened by financial performance. Based on this study, managerial ownership focuses on short-term financial gains. The implication of this study is in order to maintain a high level of CSR, it is crucial to manage the percentage of managerial ownership to be minimal in a company.